Hypocalcaemic cardiomyopathy: a description of two cases and a literature review - Martin Válek; Lenka Roblová; Ivan Raška Jr.; Dita Schaffelhoferová; Tomáš Paleček (ESC Heart Failure)
Abstract Hypocalcaemic cardiomyopathy is a rare form of dilated cardiomyopathy. The authors here present two cases in which symptomatic dilated cardiomyopathy was the result of severe hypocalcaemia. First, we report about a 26‐year‐old woman with primary hypoparathyroidism and then about a 74‐year‐old man with secondary hypoparathyroidism following a thyroidectomy. In both cases, the left ventricular systolic function improved after calcium supplementation. In the first case, a lack of compliance led to a repeated decrease of both serum calcium level and left ventricular systolic function. The authors also present a comprehensive summary of all cases of hypocalcaemic dilated cardiomyopathy that have been described in literature to date. The mean age of the affected patients was 48.3 years, of which 62% were female patients. The most common causes of hypocalcaemic cardiomyopathy are primary hypoparathyroidism (50%) and post‐thyroidectomy hypoparathyroidism (26%). In the post‐thyroidectomy subgroup, the median time for the development of hypocalcaemic cardiomyopathy is 10 years (range: 1.5 months to 36 years). Hypocalcaemic cardiomyopathy leads to heart failure with reduced ejection fraction in 87% of patients. Generally, the most common complications of hypoparathyroidism and/or hypocalcaemia are cerebral calcifications, cognitive deficit, and cataracts. Once calcium supplementation is administered, the disease has a good prognosis and, in most individuals, a significant improvement (21%) or even normalization (74%) of the left ventricular systolic function occurs.